The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4319/lo.2011.56.2.0508
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the spatial patterns in community composition of prokaryotic and eukaryotic lake plankton

Abstract: We sampled 100 small lakes in Finland for bacterio-, phyto-, and zooplankton. The lakes were located in five drainage systems, 20 lakes for each system. We tested two main predictions: that the correlation between community similarity and geographical distance (spatial distance decay) is stronger at the across-drainage than at the within-drainage system scale, and that spatial distance decay is strongest for zooplankton and weakest for bacteria. We used a combination of direct ordination, multivariate statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
95
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 47 publications
12
95
4
2
Order By: Relevance
“…The z value for different functional and phylogenetic groups was Ͻ0.0066, which is 1 to 2 orders of magnitude lower than those reported in previous studies (3,(11)(12)(13)(14)(15)(16)(17)(18). For example, Martiny et al (3) demonstrated that z values for Nitrosomonadales in salt marsh sediments varied significantly among spatial scales, with z values of 0.02 within marshes, z values of 0.14 within regions (across marshes), and no significant z value at the continental scale (across regions), using 16S rRNA gene-based PCR cloning and sequencing approaches.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…The z value for different functional and phylogenetic groups was Ͻ0.0066, which is 1 to 2 orders of magnitude lower than those reported in previous studies (3,(11)(12)(13)(14)(15)(16)(17)(18). For example, Martiny et al (3) demonstrated that z values for Nitrosomonadales in salt marsh sediments varied significantly among spatial scales, with z values of 0.02 within marshes, z values of 0.14 within regions (across marshes), and no significant z value at the continental scale (across regions), using 16S rRNA gene-based PCR cloning and sequencing approaches.…”
Section: Discussioncontrasting
confidence: 45%
“…Zhou et al (2) suggested that, based on data from GeoChip analysis, the z value for microbial communities in forest soil was 0.0624, and the z values varied considerably across different functional and phylogenetic groups (z ϭ 0.0475 to 0.0959). Other studies also showed that the z values are typically between 0.01 and 0.1 for microorganisms in various habitats (2,3,(11)(12)(13)(14)(15)(16)(17). Activated sludge is a unique microbial ecosystem, and it has high diversity, with over 700 genera and thousands of OTUs (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the results of spatial predictors are not consistent across data sets, we conclude that dispersal pathways, large scale environmental properties, or different histories of different parts of regions seem to be more important in determining regional invariance than spatial distances or the size of the region per se. This is also what Crump et al (2007) and Soininen et al (2011) concluded from studies on β-diversity of microbial plankton.…”
Section: Discussionsupporting
confidence: 52%
“…Our results revealed clear differences in the bacterial communities of lakes distributed over approximately 7° of latitude (approximately 1200 km) in summer and winter. Differences in bacterial community structure did correlate with geographic distance between lakes, indicating that at this spatial scale, the biogeography of temperate and boreal lakes in Québec appears to follow the distance-decay relationship found by previous studies (Horner-Devine et al 2004, Hewson et al 2006, Soininen et al 2011, Jones et al 2012. However, our results also show that differences in community structure among the Québec lakes were dominated by environmental factors.…”
Section: Discussioncontrasting
confidence: 49%